Improved Voltage and Frequency Control in Smart Grid using a Novel Customized Active Power Control with Smart PV Systems - Naresh Kumar (Mathematical Statistician and Engineering Applications, 2022)
During present days, the grid systems play an important role in generating self-sufficient power for customers from service providers. Moreover, the advantages of grid such as low cost, stability and wide area coverage, specifically in smart grids make its usage in a wide range. Generally, smart grid system provides self-healing abilities and allows electricity users as active participants. However, the challenges in smart grids like contingency, flexibility, reliability, and security issues still exist. This research introduces a novel approach for achieving the adaptability of smart grids with the intelligent solar photovoltaic (SPV) systems. The proposed model used Customized Active Power Control (APC) for improving the operation of SGs having minimal voltage deviations and frequency variations. The attained results demonstrate the enhanced voltage and frequency control in varying parameters such as voltage, frequency, curtailment, and de-curtailment with respect to active and reactive powers.